Job embeddedness and retention: a study among teachers in private Islamic schools in Malaysia - Juhdi, Nurita; Hashim, Junaidah; Abdul Rahman, Rozailin (Universiti Malaysia Sabah, 2018)
Malaysia is in the midst of embracing the Industrial Revolution 4.0 and is working hard to strengthen the educational sector so that the future human capital possesses high ethical values and morality. Term like internet of things become the buzzword of the day but still, Islamic education providers particularly private Islamic schools in Malaysia are still struggling to survive and coupled with high turnover rates among the teachers, they have difficulty in producing high quality Islamic education. They are in dire needs of teachers who are willing to stay and sacrifice for students. Despite the high turnover rate, there are teachers who are still willing to stay and hence, the study was conducted to investigate the reasons for the teachers to stay. Job embeddedness theory was used in this study because it was able to uncover the reasons why employees stay in organizations and thus, the study examined the relationship between job embeddedness and employee retention among teachers in private Islamic schools in Malaysia. Three hundred and ninety school teachers in private Islamic schools participated in the study and the data was collected using survey forms. The findings revealed that fit to organization, fit to Islamic school practices, fit to community, links to school and organization-related sacrifices were significantly related to employee retention. The findings contribute significantly to the school administrators. Islamic education aims to nurture the young people as the future leaders. High turnover rates could negatively affect the goal of Islamic education and thus, the administrators and the policy makers have to give attention to the pressing issue especially in the era of technological sophistication.